PENERAPAN IPTEKS BAGI KELOMPOK PETERNAK SAPI DI DESA TUMALUNTUNG KECAMATAN KAUDITAN KABUPATEN MINAHASA - Kaunang, C L; Kaunang, W B (ZOOTEC, 2018)
APPLICATION OF SCIENCE AND TECHNOLOGY FOR CATTLE BREEDING  GROUP IN TUMALUNTUNG VILLAGE  KAUDITAN SUB DISTRICT NORTH MINAHASA. Cattle’s breeding in Indonesia is generally still done traditionally, which the cattle are allowed to feed themselves, while the numbers of grass / forage become less and lower in nutritional value. This will affect on cattle productivity adversely. To overcome this, it is necessary to peform of a grass silage preservation and supplemental feeding using an urea-sugar palm-block (UGB), so the feed remains available all the time and the nutritional value becomes better. Tumaluntung is a village in KauditanSubdistrict of North Minahasa Regency, which produces brown sugar as its main crop. In this village there are several groups of cattle bereeders, among them group Mateluntung I and Mateluntung II.Pre-survey showed that the problems faced by the cattle breeders in this village were lack of knowledge by group members to raise cattle, lack of knowledge to provide qualified  of forage sustainability, lack of knowledge about making silage and UGB. Therefore, we had done an empowerment  cattle breeder groups to increase their knowledge, skills and their income. Method was carried out through counselling and training. Members of the group responded well to this application of science and technology, this can be seen from the availability of elephant grass and dwarf grass. Other products produced were silage and UGB. Keywords : Group of breeders, cattle, silage, UGB